Spatio-Temporal Change in Land Use and Land Cover of District Rajouri : A Geo-Spatial Approach - Mohd.Farooq,; Gulshan Rashid,; Sanjay Arora, (Journal of Soil and Water Conservation, 2022)
Land use and land cover is of dynamic nature and needs proper monitoring for the sake of optimum utilization of land resources. In the vicinities of smaller cities and towns commanding large rural catchments, particularly in arid and semi-arid hilly areas, the rate of such changes is far faster than other areas. Such areas are mostly in juvenile stage of development, attracting large number of people from surrounding villages to the towns, where diversified land use activities take place. This paper focuses on changes in the major land use/ land cover classes, which took place in district Rajouri during the period of25 years (1976-2001). ETM Landsat(2001) and Landsat MSS (1976) images have been used to detect such changes. Land classification and change detection has been performed by digital image processing techniques. It has been noticed that meadows have decreased by more than (75%) followed by forest cover (43%), barren land (16%) and mixed vegetation by (2.5%). Conversely, an increase has been noticed in the grasslands (400%), maize and wheat crop (65.7%) and rice crop (1.8%), resulting into shift in land use pattern.